DOI: 10.18122/b2ct4t
|View full text |Cite
|
Sign up to set email alerts
|

Using Learning Analytics to Predict Academic Success in Online and Face-to-Face Learning Environments

Abstract: This learning analytics study looked at the various student characteristics of all on-campus students who were enrolled in 100 and 200 level courses that were offered in both online and face-to-face formats during a two-year period. There is a perception that online education is either not as successful as face-to-face instruction, or it is more difficult for students. The results of this study show this is not the case.The goal of this study was to complete an in-depth analysis of student profiles addressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The correlation between semester GPA and final score in TL courses was moderately positive (r = 0.49, p < 0.01), whereas a strong positive correlation exists between the semester GPA and final score in BL courses (r = 0.65, p < 0.01). This result was consistent with the findings of [31], who achieved similar results between online and face-to-face enrollments. Conversely, a very weak positive relationship was achieved between the Kankor 3 score and the final score of students in BL courses (r = 0.16, p < 0.01), whereas the relationship between the Kankor score and the final score of students in TL was negative (r = -0.33, p < 0.01).…”
Section: Pearson Coefficient Of the Correlation Analysis Resultssupporting
confidence: 92%
“…The correlation between semester GPA and final score in TL courses was moderately positive (r = 0.49, p < 0.01), whereas a strong positive correlation exists between the semester GPA and final score in BL courses (r = 0.65, p < 0.01). This result was consistent with the findings of [31], who achieved similar results between online and face-to-face enrollments. Conversely, a very weak positive relationship was achieved between the Kankor 3 score and the final score of students in BL courses (r = 0.16, p < 0.01), whereas the relationship between the Kankor score and the final score of students in TL was negative (r = -0.33, p < 0.01).…”
Section: Pearson Coefficient Of the Correlation Analysis Resultssupporting
confidence: 92%
“…Relevant studies, such as (Berry, 2017), have reported similar findings, demonstrating that the amalgamation of factors like IP address, age, and years since graduating from a previous education can serve as an accurate differentiator between college students who are likely to successfully complete online courses and those who may encounter difficulties. This integration of data sources enables a more robust analysis, facilitating the identification of significant patterns and trends in student performance and engagement in elearning settings.…”
Section: A) Data Extraction and Integrationmentioning
confidence: 65%
“…First-year learners tend to have lower levels of college readiness as compared to learners at senior years of study. 51 This study identi¯ed a relationship between academic level, or the amount of time a learner had been attending college, and¯nal grade. For the study population, the higher the academic level, the higher the¯nal grade average for enrollments, which was in accordance to the literature.…”
Section: Results Of Analysismentioning
confidence: 99%